2000
DOI: 10.1037/0021-843x.109.2.345
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of "subthreshold" depressive symptoms.

Abstract: There is active debate regarding whether diagnosable depression exists on a continuum with subthreshold depressive symptoms or represents a categorically distinct phenomenon. To address this question, multiple indexes of dysfunction (psychosocial difficulties, mental health treatment history, and future incidence of major depression and substance abuse/dependence) were examined as a function of the extent of depressive symptoms in 3 large community samples (adolescent, adult, and older adult; N = 3,003). Incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
180
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 437 publications
(186 citation statements)
references
References 41 publications
(46 reference statements)
4
180
1
1
Order By: Relevance
“…Fava and Tossani [31] reviewed the evidence for this, drawing predominantly on association studies. The authors emphasized three key issues: (1) that anxiety and irritability are commonly observed in the prodromal phase of depression [30,32,33,34,35]; (2) that subthreshold or minor depression is implicated as a risk factor for the development of major depression, which reinforces the notion that depressive symptoms occur on a continuum rather than in discrete categories [36,37,38], and (3) that these symptoms are present in the first and subsequent episodes of major depression, which may inform efforts toward relapse prevention [31]. Building on Fava’s work, this notion of a prodrome has the potential to provide a recognizable point of intervention to prevent the onset of a first episode.…”
Section: A Prodrome Of Depressive Disordersmentioning
confidence: 94%
See 2 more Smart Citations
“…Fava and Tossani [31] reviewed the evidence for this, drawing predominantly on association studies. The authors emphasized three key issues: (1) that anxiety and irritability are commonly observed in the prodromal phase of depression [30,32,33,34,35]; (2) that subthreshold or minor depression is implicated as a risk factor for the development of major depression, which reinforces the notion that depressive symptoms occur on a continuum rather than in discrete categories [36,37,38], and (3) that these symptoms are present in the first and subsequent episodes of major depression, which may inform efforts toward relapse prevention [31]. Building on Fava’s work, this notion of a prodrome has the potential to provide a recognizable point of intervention to prevent the onset of a first episode.…”
Section: A Prodrome Of Depressive Disordersmentioning
confidence: 94%
“…Increasingly specialized and intensive interventions, including the use of psychopharmacological treatments, can be reserved for those with more severe disorders and complex needs at later stages of illness, and are more suited to delivering in specialized settings [41] (table 1). Although guidelines for a stepped model of care, consistent with a staging model for depressive disorders, have been developed [37, 70,][71], the notion that interventions can be matched to a stage of illness has not yet been elaborated. In the remainder of the paper, we will present preliminary evidence to support this premise.…”
Section: Interventions In the Early Stages Of Depressive Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…Subthreshold symptoms have gained prominence as depression is increasingly recognised as being on a spectrum [17]. Studies in children and adolescent populations have generally used prospective epidemiological designs to measure subthreshold symptoms of depression and their predictive value, rather than the retrospective designs traditionally associated with prodrome research [10].…”
Section: Introductionmentioning
confidence: 99%
“…Depressive disorders are highly associated with behavioral problems, somatic complaints, and other psychiatric disorders and behaviors, such as anxiety, suicide attempts, conduct disorder, and substance abuse (Birmaher et al, 1996;Eapen & Cˇrnc ˇ ec, 2012). However, not only clinically significant depression but also 'subthreshold' depressive symptoms have connections to psychosocial impairment and the use of mental health services, and therefore the conceptualization of depression as a continuum is necessary (Angold, Costello, Farmer, Burns, & Erkanli, 1999;Lewinsohn, Solomon, Seeley, & Zeiss, 2000). In additional to the short-term problems, depression can have a negative longterm impact on mental health, including increased risk of suicide, abuse of alcohol and other substances, physical problems, disturbances in global functioning and interpersonal relationships, and the recurrence of depression in later adolescence and adulthood (Birmaher et al, 1996;Lewinsohn et al, 1994).…”
mentioning
confidence: 99%